2012
DOI: 10.3892/ijmm.2012.924
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate prevents TNF-α-induced NF-κB activation thereby upregulating ABCA1 via the Nrf2/Keap1 pathway in macrophage foam cells

Abstract: Abstract. The ATP-binding membrane cassette transporter A1 (ABCA1) plays a protective role in the development of atherosclerosis for the reverse cholesterol transport process. Epigallocatechin-3-gallate (EGCG), which exists abundantly in green tea, exerts an anti-atherosclerotic effect via antiinflammatory and metabolic regulation activities. Many genes and proteins related to lipid metabolism are involved in the lowering cholesterol effects of EGCG. However, effects of EGCG on ABCA1 have rarely been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
3
23
0
1
Order By: Relevance
“…The infliximab concentration used in this study is within the therapeutic range for RA and is close to the average trough level of 3.3  μ g/mL [19, 20]. Our finding that TNF- α decreases ABCA1 and LXR- α is consistent with previous reports in macrophages and other cell types [2124].…”
Section: Resultssupporting
confidence: 91%
“…The infliximab concentration used in this study is within the therapeutic range for RA and is close to the average trough level of 3.3  μ g/mL [19, 20]. Our finding that TNF- α decreases ABCA1 and LXR- α is consistent with previous reports in macrophages and other cell types [2124].…”
Section: Resultssupporting
confidence: 91%
“…Although previous studies showed that SFN activated NRF2 and ameliorated diabetes-induced testicular apoptotic cell death without knowing the expression of Keap1 [5, 6], we speculate that inhibition of KEAP1 function by SFN could be the mechanism through which SFN activated NRF2 in these studies. Similar to SFN, EGCG is also known to activate NRF2 by inactivating KEAP1 [46, 47]. EGCG is speculated to directly interact with the cysteine residues present in KEAP1, thereby stimulating NRF2 dissociation from KEAP1 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Because of our recently reported effects of inflammation on UFs26 and possible anti-inflammatory effects of EGCG,27,28 we assessed specific markers of inflammation in all participants. We measured the levels of two serum inflammation biomarkers (interleukin 6 and tumor necrosis factor-α)29,30 and one urinary biomarker (isoprostane)31 of inflammation. All participants underwent endometrial biopsy at baseline (visit 1) and at the end of the study after 4 months (visit 5) to confirm the presence of normal endometrium and to ensure the safety of EGCG treatment on endometrium histology 32,33.…”
Section: Methodsmentioning
confidence: 99%